Uncovering a novel binding trench in ERRα: insights from molecular simulations - Hegazy, Lamees (Frontiers in Molecular Biosciences, 2025)
Although estrogen-related receptor α (ERRα) holds significant therapeutic potential for treating various disorders, developing selective agonists remains challenging due to the poor pharmacokinetics and limited selectivity of current ligands. This study presents unconstrained molecular dynamics simulations of ERRα bound to an agonist ligand, uncovering dynamic ligand-binding behavior as the ligand shifts between two orientations: one in the orthosteric pocket and another in a newly identified trench adjacent to this site. The free energy landscape reveals that both binding orientations are comparably populated, with an accessible transition pathway between them. The identification of this novel binding trench expands our understanding of ERRα′s ligand binding domain, offering new avenues for small-molecule drug discovery and selective modulation of ERRα activity.